Transcriptional Inhibition of lncRNA gadd7 by CRISPR/dCas9-KRAB Protects Spermatocyte Viability - Zhao, Jun; Ma, Wenmin; Zhong, Yucheng; Deng, Hao; Zhou, Bingyu; Wu, Yaqin; Yang, Meiqiong; Li, Huan (Frontiers in Molecular Biosciences, 2021)
Our previous study found that lncRNA gadd7 was up-regulated in the semen of varicocele patients, and could promote the apoptosis of mouse spermatocytes and inhibit their proliferation. Therefore, we further explored whether down-regulation of Gadd 7 expression could protect the viability of spermatocytes. Here we designed specific sgRNAs targeting the ORF region of gadd7, and constructed a CRISPR-dCas9-KRAB system that effectively inhibits gadd7 at the transcriptional level. The CRISPRi system can effectively prevent the apoptosis of spermatocytes and enhance their proliferation, which is expected to provide a potentially effective molecular intervention method for the treatment of male infertility caused by varicocele.